1986
DOI: 10.1007/bf01800058
|View full text |Cite
|
Sign up to set email alerts
|

3‐hydroxy‐3‐methylglutaryl‐coenzyme a lyase deficiency: Report of five new patients

Abstract: Five new patients are reported and the pathogenesis of the hypoglycaemia without ketogenesis is discussed. This report extends a recent review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
2

Year Published

1989
1989
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 16 publications
0
30
0
2
Order By: Relevance
“…Initial symptoms may include poor feeding, vomiting, diarrhea, followed by further complication as hypotonia, hypothermia, lethargy, cyanosis and apnea. (Schutgens et al, 1979;Gibson et al, 1988a;Gibson et al, 1988b). In some cases the progresive lowered state of consciousness leads to coma and subsequent death (Wysocki et al, 1986).…”
Section: Acute Crisismentioning
confidence: 99%
See 1 more Smart Citation
“…Initial symptoms may include poor feeding, vomiting, diarrhea, followed by further complication as hypotonia, hypothermia, lethargy, cyanosis and apnea. (Schutgens et al, 1979;Gibson et al, 1988a;Gibson et al, 1988b). In some cases the progresive lowered state of consciousness leads to coma and subsequent death (Wysocki et al, 1986).…”
Section: Acute Crisismentioning
confidence: 99%
“…Chronic complications are uncommon but include: hepatomegalia, macrocephalia (Gibson et al, 1988b;Stacey et al, 1985) microcephalia (Lisson et al, 1981) and delayed development (Gibson et al, 1994). It has been reported that organs such as the brain, the liver and occasionally the pancreas and the heart are affected (Gibson et al, 1994;Leung et al, 2009;Muroi et al, 2000a;Urganci et al, 2001;Wilson et al, 1984;Zafeiriou et al, 2007;Zoghbi et al, 1986).…”
Section: Chronic Complicationsmentioning
confidence: 99%
“…Abbreviations: HMG = 3-hydroxy-3-methylglutaric; HMG-CoA = 3-hydroxy-3-methylglutaryl-CoA; 3-MCR-CoA = 3-methylcrotonyl-CoA; 3-MGC = 3-methylglutaconic; 3-MGC-CoA = 3-methylglutaconyl-CoA; 3-MG = 3-methylglutaric; M-5-P = mevalonate-5-pyrophosphate published in recent years [15,32,38]. In contrast, publications on isolated deficiencies of 3-methylcrotonyl-CoA carboxylase (3-MCR-CoA carboxylase: E.C.…”
Section: Correspondence To: K M Gibsonmentioning
confidence: 99%
“…The disorder is characterized biochemically by greatly increased concentrations of several characteristic organic acids in blood and urine, including 3-hydroxy-3-methylglutaric and, 3-methyiglutaric acid, 3-methylglutaconic acid and 3-hydroxyisovaleric acid, and by demonstrably deficient activity of HMG CoA lyase activity in blood leukocytes and cultured skin fibroblasts H~ihnel, 1976, 1986;Stacey et al, 1985;Gibson et al, 1988). The disorder may be severe and potentially lethal with patients presenting with recurrent episodes that resemble Reye syndrome, with severe hypoglycaemia, hyperammonaemia, encephalopathy and metabolic acidosis, and permanent neurological damage occurring in some patients surviving late-treated episodes.…”
mentioning
confidence: 99%